Bioerosion on late Quaternary planktonic Foraminifera related to paleoproductivity in the western South Atlantic - Cristiane Fraga Frozza; Maria Alejandra G Pivel; Jaime Yesid Suárez-Ibarra; Matias do Nascimento Ritter; João Carlos Coimbra (PANGAEA, 2020)
These datasets include the relative abundances of planktonic foraminifera, relative abundances of drilled specimens, stable isotope data and age model results of sediment core SAT-048A.